Psicologia humanista de Carl Rogers: recepção e circulação no Brasil - Paulo Coelho Castelo Branco (2015)
Thesis divided in four studies whose central idea is that all Psychology is local and expresses in its developmental context a hybridization that depends on its historical processes of reception and circulation. This idea was applied to the argument that the Humanist Psychology of Carl Rogers, in its development in the U.S.A. and in Brazil, was sensible to these processes, with specific aspects distinguishing them in each place. The perspective chosen to investigate such argument is based on the relations between the Person-Centered Approach (PCA) and Phenomenology. It should be noted that all studies are independent, however each of them refers historically to this perspective in its own way. The first study is theoretical and is about the notion of reception and circulation and their implications to historical research in Psychology. The second one is inspired by Josef Broek's historiographical approach, analyzing the several relations that Rogers established to Phenomenology. To do so, the second study is divided in two analyses: one that reviews the number of philosophers quoted and referenced by Rogers throughout his work; other that examines seven moments when Rogers established relations with the movement of reception of Phenomenology by the American Psychology, from 1940 to 1960. In fact, Rogers only quoted and referenced one phenomenologist, Martin Heidegger. The Phenomenology mentioned by Rogers isn't the philosophical one, which he saw with caveats, but an American paradigm of empirical science and personality studies. The third study, again inspired by Broek's historiography, divides the moments of reception of Rogers' Humanist Psychology in Brazil, from 1945 to 1990, analyzes the Rogerian works translated to Brazilian Portuguese from 1970 to 2000, and performs a bibliographic review to understand the kind of PCA that circulates in Brazilian periodicals from 2002 to 2014. The results from the third study point out that: phenomenological PCA was established in at the end of 1980s crisis; currently theres a shortage in articles production about Rogers; theres hegemony of theoretical and clinical productions; Brazilian PCA differs from Rogerian PCA as it establishes, in its theoretical discussions, a relation to the European phenomenological philosophy. The fourth study reflects, epistemic and historically, the reception and circulation of the Rogerian notion of consciousness in Brazilian PCA of phenomenological lineage. Noteworthy points up to Brazil scene, where there is an epistemic tension in approaching Rogers' Humanist Psychology to Phenomenology, as the Rogerian idea of consciousness comes from a pragmatic-functional base that differs from a phenomenological one; however, historically, that relation can be understood in terms of local development. In the course of the studies the conclusion is that there is a series of theoretical and conceptual potentialities in approaching PCA to Phenomenology. The historiographical attitude toward this relation has, in its core, a comprehensive aspect to the local dimensions affecting historically Rogers' Humanist Psychology and Brazilian PCA.